Enhancing ESG Disclosure: The Role of Profitability, Financial Slack, and Board Gender Diversity in Indonesian and Malaysian Banks Sector - Aulia, Azwani; Lastari, Adria Wuri; Dillak, Vaya (GREENOMIKA, 2025)
This study employs a quantitative method with multiple regression analysis to examine the influence of profitability, financial slack, and board gender diversity on ESG disclosure among companies listed on the Jakarta and Kuala Lumpur Stock Exchanges. The population consists of 234 companies, with a sample of 60 companies selected through purposive sampling method. Data were analyzed using SPSS software for hypothesis testing. The results indicate that profitability, financial slack, and board gender diversity significantly enhance ESG disclosure by enabling companies to allocate resources more effectively for social and environmental activities. The study’s implications highlight the importance of digitalization in accelerating data collection and improving the accuracy and transparency of ESG disclosures, enabling companies to be more accountable in sustainability reporting. These findings contribute valuable insights for advancing sustainable and transparent corporate governance practices.